ALAT PELACAK BERBASIS LONG RANGE WIDE AREA NETWORK (LORAWAN) - Irawati Irawati; Fransiskus Yulius Roi; Titus Yobilio Agung; Muhammad Lutfi (Institut Teknologi dan Bisnis Swadharma, 2022)
Long Range Wide Area Network (LoRaWAN) is a type of network for wireless telecommunications area designed to support long distance communication. LoRaWAN can be used on communication networks that have a wide range using end devices. LoRaWAN offers various advantages that are able to answer the application of IoT applications, but the current application of LoRaWAN technology is still very limited, so simulation and analysis of the extent to which LoRaWAN technology can be simulated in urban areas in Indonesia is needed. And in this tool, we developed a loawan to track location with a loawan GPS module capable of sending GPS data with radio signals without using the internet or cellular data